CLINICAL OUTCOMES OF PRIMARY PERCUTANEOUS CORONARY INTERVENTION USING DES VS BMS In ACUTE CORONARY SYNDROME PATIENTS WITH LEFT ANTERIOR DESCENDING ARTERY INVOLVEMENT: A COMPARATIVE STUDY - DURRANI , T; QADEER , A; JUNAID , M; HUSSAIN , I; KHAN , F; DURRANI , H (Biological and Clinical Sciences Research Journal, 2024)
Acute coronary syndrome (ACS) with left anterior descending (LAD) artery involvement often leads to more extensive myocardial infarction. Choosing between drug-eluting stents (DES) and bare-metal stents (BMS) for revascularisation in these patients is a topic of clinical relevance. While drug-eluting stents are the gold standard, bare-metal stents remain an essential option for patients with specific considerations such as an inability to complete the recommended duration of DAPT, advanced age, concomitant oral anticoagulation, cancer, affordability issues, increased bleeding risk, and planned noncardiac surgery within the next year. Objective: This study aimed to compare the clinical outcomes of ACS patients with LAD involvement treated with either DES or BMS during primary PCI.Methods: A retrospective cohort study was conducted between January 1, 2021, and December 31, 2023, at a tertiary care center. A total of 200 ACS patients with LAD involvement who underwent primary PCI were included. Patients were grouped based on the type of stent used (DES or BMS). Data on patient demographics, comorbidities, procedural details, and outcomes were collected. Major adverse cardiovascular events (MACE), including all-cause mortality, myocardial infarction (MI), and target lesion revascularisation (TLR), were assessed. Kaplan-Meier survival analysis and Cox proportional hazards models were used to analyse outcomes. Results: MACE occurred in 48 patients (24%) during the one-year follow-up. Patients treated with DES experienced significantly fewer events (p < 0.001) compared to those receiving BMS. Diabetes mellitus and chronic kidney disease were independent predictors of adverse outcomes (p = 0.006 and p < 0.001, respectively).Conclusion: Primary PCI using DES in ACS patients with LAD involvement is associated with better clinical outcomes compared to BMS, particularly in high-risk populations. These findings suggest that DES should be the preferred stent type for this patient group to reduce adverse events and improve long-term survival.